Colorimetric characterization, texture and sanitary quality of breads added with Creole corns and Curcuma longa (Superficies y Vacío, 2022)
The objective of this research was to characterize the color, texture and sanitary quality of bread added with creole corn and turmeric. Fourteen different breads were made using six types of corn (M1, M2, M3, M4, M5 and M6). The main findings were a) The color of the corn, nixtamalized flours and doughs had a significant difference (p < 0.05) when comparing mean values of Luminosity, a* and b* parameters. Blue and reddish corn M2 (37.01), M3 (44.06) and M6 (41.07) and, yellow and yellow orange M1 (21.26), M4 (15.92) and M5 (26.01) presented the lowest values in L* and highest in b*, respectively. The smallest difference in color ?E found in the transformation process from corn to flour and dough, was for yellow corn. b) In corn bread, significant differences in variable a* were found when comparing the same type of bread for three consecutive days, in breads BM1, BM5 and BM6, with a decrease of 7.5, 2.6 and 16.9%, with respect to the first day. c) The sanitary quality of wheat bread improves with the addition of nixtamalized corn and turmeric. The blue and red corn (M2, M3 and M6) showed the lowest number of fungal colonies in the breads with corn additives. d) The hardness of the bread made with creole corn and turmeric did not show differences during three consecutive days, benefiting its conservation. The yellow corn and turmeric bread BM1-C showed increases in the hardness on days 2 and 3, and the yellow corn and turmeric bread BM1-C showed increases in the hardness on days 2 and 3.